Development of the Parent Form of the Preschool Children's Communication Skills Scale and Comparison of the Communication Skills of Children with Normal Development and with Autism Spectrum Disorder - AYDIN, AYDAN (EDAM, 2016)
This study aims at developing an assessment scale for identifying preschool children's communication skills, at distinguishing children with communication deficiencies and at comparing the communication skills of children with normal development (ND) and those with autism spectrum disorder (ASD). Participants were 427 children of up to 6 years of age with ND (45% female, 55% male) and 76 children from ages 1-6 years with ASD (25% female, 75% male. Exploratory factor analysis and principal component analysis were applied to maintain construct validity. The total loads of factors were between 65.32% (0-1 module) and 75.75% (4-5 module). The Cronbach's alpha internal consistency coefficient value was high for all the modules (alpha(min) = .93; alpha(max) = .97). The items in all the modules are highly correlated to the total score of the module (r(min) = .35; r(max) = .91; p<.001), and the high/low groups of the items included in all the modules are distinctive (t(n) = -9.95; t(max) = -52.67; p<.001). Results of the independent samples t-test applied to compare children with ND and children with ASD revealed the difference in the means of all the modules is significant (t(min) = 6.30; p<.001). In conclusion, all the modules in the parent form are sufficiently reliable and valid; thus, the form can be used to distinguish children with ND from those with ASD in terms of their communication skills.
Keywords: Communication; Preschool; Autism spectrum disorder; Parents' opinions; Scale development; PRELINGUISTIC PREDICTORS; SOCIAL COMMUNICATION; POINTING GESTURE; JOINT ATTENTION; EARLY LANGUAGE; PLAY; DIAGNOSIS; COGNITION; MOTHERS